RETRACTED: Toxicity Evaluation of New Engineered Nanomaterials in Zebrafish - Brundo, Maria V.; Pecoraro, Roberta; Marino, Fabio; Salvaggio, Antonio; Tibullo, Daniele; Saccone, Salvatore; Bramanti, Vincenzo; Buccheri, Maria A.; Impellizzeri, Giuliana; Scuderi, Viviana; Zimbone, Massimo; Privitera, Vittorio (Frontiers in Physiology, 2016)
The effect of the nanoparticles on the marine organisms, depends on their size, chemical composition, surface structure, solubility and shape. In order to take advantage from their activity, preserving the surrounding environment from a possible pollution, we are trying to trap the nanoparticles into new nanomaterials. The nanomaterials tested were synthesized proposing a ground-breaking approach by an upside-down vision of the Au/TiO2nano-system to avoid the release of nanoparticles. The system was synthesized by wrapping Au nanoparticles with a thin layer of TiO2. The non-toxicity of the nano-system was established by testing the effect of the material on zebrafish larvae. Danio rerio o zebrafish was considered a excellent model for the environmental biomonitoring of aquatic environments and the Zebrafish Embryo Toxicity Test is considered an alternative method of animal test. For this reason zebrafish larvae were exposed to different concentrations of nanoparticles of TiO2 and Au and new nanomaterials. As biomarkers of exposure, we evaluated the expression of metallothioneins by immunohistochemistry analysis and western blotting analysis also. The results obtained by toxicity test showed that neither mortality as well as sublethal effects were induced by the different nanomaterials and nanoparticles tested. Only zebrafish larvae exposed to free Au nanoparticles showed a different response to anti-MT antibody. In fact, the immunolocalization analysis highlighted an increase of the metallothioneins synthesis.